Delirium assessment in critically ill older adults: considerations during the COVID-19 pandemic (2020)
Older adults are particularly vulnerable during the Coronavirus disease 2019 (COVID-19) pandemic, as higher age increases risk for both delirium and COVID-19- related death. Despite the healthcare system limitations and the clinical challenges of the pandemic, delirium screening and management remains an evidence-based cornerstone of critical care. In this review, we discuss practical recommendations for delirium screening in the COVID-19 pandemic era, tips for training healthcare workers in delirium screening, validated tools for detecting delirium in critially ill older adults, and approaches to special populations of older adults (e.g., sensory impairment, dementia, acute neurological injury).